A high ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries, its preparation method and application.

CN122025692BActive Publication Date: 2026-09-01GUIZHOU ZHIXI TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610162620.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-02-05
Publication Date
2026-09-01
Estimated Expiration
2046-02-05

AI Technical Summary

Technical Problem

[0011]有鉴于此,本发明开发了一种钒电池用高离子选择性全氟磺酸离子膜及其制备方法和应用,成功提高了离子膜的电导率、降低了钒离子渗透率,提高了离子选择性,且兼具优异稳定性,有效解决了传统全氟磺酸膜离子选择性差、长期稳定性不足的关键瓶颈

Benefits of technology

[0050] (1) Breakthrough in ion selectivity: While maintaining a proton conductivity comparable to or even higher than that of Nafion 212 (>90 mS/cm), the membrane of this invention significantly reduces vanadium ion permeability to 0.95 × 10⁻⁶ mS/cm. -7 The ion selectivity of the membrane was on the order of cm²/min. Ultimately, the ion selectivity of the membrane reached 10-16 times that of the Nafion 212 membrane of the same thickness. This leap forward is due to the super synergistic effect between the "-OH-rich MXene core", the "bimodal porous COF shell", and the "dual crosslinking interface", which cannot be achieved by a single improvement or simple superposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses a high-ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries, its preparation method, and its applications. It belongs to the field of electrochemical energy storage and functional polymer materials technology. The ion-exchange membrane uses perfluorosulfonic acid resin as a matrix, containing a functionalized core-shell hybrid filler and a dual-interface crosslinking network. The filler core layer is a mildly etched pretreated -OH-rich, low-F MXene nanosheet, and the shell layer is an SNW-1 type covalent organic framework with a bimodal pore size distribution grown in situ using a gradient heating method. The dual-crosslinking network is synergistically composed of a silane coupling agent chemically anchored to MXene and a flexible organic crosslinking agent. Through the synergistic effect of these three components, the membrane exhibits high proton conductivity, extremely low vanadium ion permeability, high ion selectivity, and excellent stability under accelerated aging in strong acid, effectively solving the key bottlenecks of poor ion selectivity and insufficient long-term stability in traditional perfluorosulfonic acid membranes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage and functional polymer materials technology, and more specifically to a high ion selectivity perfluorosulfonic acid ion membrane for vanadium batteries, its preparation method, and its application. Background Technology

[0002] Vanadium redox flow batteries (VRFBs) have shown great promise in large-scale energy storage due to their high safety, long cycle life, and the ability to independently design power and capacity. As a core component of VRFBs, the ion exchange membrane plays a dual role: conducting protons to close the circuit while simultaneously preventing the cross-permeation of vanadium ions in the positive and negative electrode electrolytes. Therefore, the ion selectivity of the membrane (the ratio of proton conductivity to vanadium ion permeability) is a key indicator determining the battery's coulombic efficiency, energy efficiency, and lifespan.

[0003] Currently, commercially available perfluorosulfonic acid (PFSA) membranes (such as the Nafion series) are widely studied due to their excellent chemical stability and high proton conductivity. However, the ion transport channels formed by ion clusters within PFSA membranes (typically 3-5 nm) are much larger than those for hydrated protons (approximately 0.24 nm) and hydrated vanadium ions (V). n+ The small size (>0.6 nm) of the vanadium ions results in extremely weak size sieving ability for vanadium ions, causing severe vanadium ion cross-contamination. This not only leads to a general coulombic efficiency of less than 90% in batteries, but also causes imbalance of active materials and capacity decay, creating an inherent contradiction where proton conductivity and ion selectivity are difficult to achieve simultaneously.

[0004] To improve the ion selectivity of PFSA membranes, researchers mainly employ two strategies: blending modification and composite membranes. Among these, introducing covalent organic framework materials with regular nanopores as molecular sieve fillers has become a research hotspot in recent years. For example, there are existing reports of in-situ growth of SNW-1 type COF on graphene oxide (GO) surfaces and its composite with PFSA to enhance selectivity. Another study in-situ grew SNW-1 COF on the surface of two-dimensional MXene nanosheets and used it in sulfonated polyether ether ketone (SPEEK) membranes, utilizing the hydrophilicity and layered structure of MXene to assist proton conduction and increase ion diffusion pathways.

[0005] However, the aforementioned existing technologies still face the following insurmountable bottlenecks in the development of PFSA-based composite films for high-performance, long-life VRFB applications:

[0006] The filler-matrix interface is fragile: highly polar hybrid fillers (such as MXene / COF) have poor compatibility with hydrophobic PFSA matrices, and physical blending easily leads to interface defects. In long-term strong acid and strong oxidizing environments, the interface is prone to debonding, forming non-selective ion leakage channels, and performance deteriorates rapidly.

[0007] Discontinuous proton conduction network: There is a lack of efficient proton exchange "bridges" between the proton conduction sites (such as -OH) on the surface of fillers such as MXene and the sulfonate ion cluster network of PFSA. The resistance to proton cross-interface transport is large, and the proton conduction advantage of the filler cannot be effectively converted into macroscopic membrane performance.

[0008] Mass transfer limitations of single microporous structure: Conventional COF only has micropores (<2 nm), which can effectively sieve vanadium ions, but also cause steric hindrance and diffusion limitation on the transport of hydrated protons. Especially when pursuing high current density, it becomes a bottleneck restricting proton conduction and it is difficult to truly break the "conductivity-selectivity trade-off".

[0009] The intrinsic surface properties of MXene are unfavorable: the surface of MXene prepared by the traditional hydrofluoric acid etching method is rich in hydrophobic -F groups, which not only have weak proton affinity, but also hinder the uniform nucleation and growth of COF and the interfacial bonding with polymers.

[0010] Therefore, developing a PFSA-based composite membrane that can fundamentally and synergistically solve the problems of interface compatibility, proton transport continuity, and multi-scale ion sieving is of great significance for promoting the commercialization of VRFB technology. Summary of the Invention

[0011] In view of this, the present invention develops a high ion-selectivity perfluorosulfonic acid ion membrane for vanadium batteries, its preparation method and application, which successfully improves the conductivity of the ion membrane, reduces the vanadium ion permeability, improves the ion selectivity, and also has excellent stability, effectively solving the key bottlenecks of poor ion selectivity and insufficient long-term stability of traditional perfluorosulfonic acid membranes.

[0012] To solve the above-mentioned technical problems, this application adopts the following technical solution:

[0013] The primary objective of this application is to provide: a high ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries, said ion-exchange membrane comprising:

[0014] Perfluorosulfonic acid polymer matrix;

[0015] A functionalized core-shell hybrid filler uniformly dispersed in the perfluorosulfonic acid polymer matrix, wherein the functionalized core-shell hybrid filler comprises:

[0016] a) Core layer: The core layer is an MXene nanosheet that has undergone mild etching pretreatment, and the molar ratio of -F functional groups to -OH functional groups in the pretreated MXene nanosheet is less than 0.5:1;

[0017] b) Shell: The shell is an SNW-1 type covalent organic framework layer grown in situ on the surface of pretreated MXene nanosheets. The SNW-1 type covalent organic framework layer has a bimodal pore size distribution, including inherent micropores of 0.5-0.8 nm and mesopores of 2-5 nm generated in situ within the SNW-1 type covalent organic framework layer.

[0018] A dual-interface cross-linked network, which is composed of the following substances:

[0019] i. A silane coupling agent, wherein one end of the silane coupling agent can form a Si-O-Ti covalent bond with the -OH group on the surface of MXene, and the other end contains an amino or epoxy group that can interact with the perfluorosulfonic acid polymer matrix;

[0020] ii. A flexible organic crosslinking agent, which is uniformly distributed in a perfluorosulfonic acid matrix, generates physical-chemical synergistic crosslinking points through hydrogen bonding, ionic interactions and physical entanglement;

[0021] The functionalized core-shell hybrid filler has a mass fraction of 0.5-5 wt% in the ion exchange membrane.

[0022] The total mass fraction of the silane coupling agent and the flexible organic crosslinking agent is 0.1-1.5 wt%, and the mass ratio of the two is 1:0.2-1:1.

[0023] As a preferred technical solution, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0024] As a preferred technical solution, the flexible organic crosslinking agent is polyethylene glycol diglycidyl ether.

[0025] Another object of this application is to provide a method for preparing the high ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries, comprising the following steps:

[0026] (1) Mild etching pretreatment of MXene nanosheets:

[0027] Ti3AlC2 MAX phase powder was dispersed in a mixed etchant and reacted with gentle stirring at 30-50℃ for 12-36 h. After the reaction, the product was centrifuged and washed until neutral to obtain a multilayer MXene etching product in which interlayer Al was selectively etched away. The multilayer MXene etching product was then subjected to low-power ultrasonic exfoliation under a protective atmosphere to dissociate the interlayers and obtain a dispersion of pretreated MXene nanosheets with one or fewer layers.

[0028] (2) In-situ growth of gradient bimodal aperture SNW-1 type covalent organic framework layer:

[0029] The dispersion of the pretreated MXene nanosheets obtained in step (1) was mixed with 1,3,5-tricarboxymethyl phloroglucinol, 1,4-diaminobenzene and glacial acetic acid as catalyst, and the reaction was carried out by gradient heating method to obtain an SNW-1 type covalent organic framework layer with bimodal pore size distribution grown in situ on the surface of the pretreated MXene nanosheets, that is, a core-shell hybrid filler of MXene and SNW-1 type covalent organic framework.

[0030] The gradient heating method includes: first reacting at 0-10℃ for 2-6 hours, then heating to 60-80℃ at a rate of 0.5-1℃ / min, and continuing the reaction at this temperature for 20-40 hours; through this gradient heating method, an SNW-1 type covalent organic framework layer with a bimodal pore size distribution is grown in situ on the MXene surface to obtain a core-shell hybrid material of MXene and SNW-1 type covalent organic framework;

[0031] (3) Preliminary interface modification of hybrid fillers:

[0032] The core-shell hybrid filler obtained in step (2) is dispersed in anhydrous ethanol, a silane coupling agent is added, and the mixture is refluxed at 60-80℃ for 4-8 hours to obtain a hybrid filler with a surface grafted silane coupling agent.

[0033] (4) Preparation of casting solution and secondary cross-linking of interface:

[0034] The hybrid filler with surface-grafted silane coupling agent obtained in step (3), perfluorosulfonic acid resin solution and flexible organic crosslinking agent are dissolved in organic solvent and a uniformly dispersed casting solution is formed under ultrasonication and stirring.

[0035] (5) Solution casting and in-situ curing:

[0036] The casting solution obtained in step (4) is cast onto a flat substrate and subjected to gradient temperature drying: first, it is dried at 40-60℃ for 2-4 hours to evaporate most of the solvent and form a preliminary film, and then treated at 100-130℃ for 4-10 hours. During this stage, the silane coupling agent and the flexible crosslinking agent work synergistically to undergo an in-situ crosslinking reaction with the perfluorosulfonic acid matrix to form a double crosslinking network; finally, it is heat-treated at 140-160℃ for 0.5-2 hours to obtain the high ion selectivity perfluorosulfonic acid ion membrane.

[0037] As a preferred technical solution, the mass-to-volume ratio of the Ti3AlC2 MAX phase powder to the mixed etchant in step (1) is 1 g : 30-60 mL;

[0038] The mixed etchant is an aqueous solution of concentrated hydrochloric acid and lithium fluoride, wherein the final concentration of concentrated hydrochloric acid in the mixed etchant is 6-9 M and the final concentration of lithium fluoride is 0.5-2.0 M.

[0039] The low-power ultrasonic ablation process is as follows: ultrasonic ablation is performed for 0.5-2 hours under argon or nitrogen protection with a power of 50-150 W.

[0040] As a preferred technical solution, the gradient heating procedure in step (2) is as follows: first react at 5℃ for 4 hours, then heat to 70℃ at 0.8℃ / min, and maintain at 70℃ for 30 hours.

[0041] As a preferred technical solution, in step (2), based on the mass of MXene nanosheets contained in the pretreated MXene nanosheet dispersion, the amount of 1,3,5-tricarboxymethyl phloroglucinol added is 10-40 mmol / g; the molar ratio of 1,4-diaminobenzene to 1,3,5-tricarboxymethyl phloroglucinol is 1.5-2.0:1; and the amount of glacial acetic acid catalyst added accounts for 3-8 vol of the total volume of the reaction system.

[0042] As a preferred technical solution, the silane coupling agent in step (3) is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0043] As a preferred technical solution, the dispersion concentration of the core-shell hybrid material in anhydrous ethanol in step (3) is 2-10 mg / mL; the amount of silane coupling agent added is 5-20% of the mass of the core-shell hybrid material.

[0044] As a preferred technical solution, the flexible organic crosslinking agent in step (4) is polyethylene glycol diglycidyl ether;

[0045] The organic solvent in step (4) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide;

[0046] In step (4), the mass ratio of the hybrid filler of the surface-grafted silane coupling agent to the dry weight of the perfluorosulfonic acid resin is 0.5-5:100; the total solid content of the casting solution is 5-15 wt%.

[0047] Another object of this application is to provide: a vanadium redox flow battery, which uses the high ion selectivity perfluorosulfonic acid ion membrane or the high ion selectivity perfluorosulfonic acid ion membrane prepared by the method as the battery separator.

[0048] As a preferred technical solution, at a current density of 150 mA cm⁻¹ -2 Under the conditions of charge and discharge testing, the average coulombic efficiency is not less than 99.0%, the average energy efficiency is not less than 90.0%, and after 3000 charge and discharge cycles, the battery capacity retention rate is not less than 97%.

[0049] As can be seen from the above technical solution, compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) Breakthrough in ion selectivity: While maintaining a proton conductivity comparable to or even higher than that of Nafion 212 (>90 mS / cm), the membrane of this invention significantly reduces vanadium ion permeability to 0.95 × 10⁻⁶ mS / cm. -7 The ion selectivity of the membrane was on the order of cm² / min. Ultimately, the ion selectivity of the membrane reached 10-16 times that of the Nafion 212 membrane of the same thickness. This leap forward is due to the super synergistic effect between the "-OH-rich MXene core", the "bimodal porous COF shell", and the "dual crosslinking interface", which cannot be achieved by a single improvement or simple superposition.

[0051] (2) Combining high conductivity and high selectivity, breaking the traditional trade-off: This invention successfully solves the inherent contradiction between proton conduction and vanadium ion blocking by using the dual design of "microporous sieving + mesoporous fast transmission" in the COF shell and the continuous proton channel constructed by the dual cross-linked network, thus achieving simultaneous optimization of the performance of both.

[0052] (3) Exhibits outstanding long-term operational stability: In the extreme accelerated aging test at 90℃ and 3.0 M H2SO4, the ion selectivity coefficient of the membrane of the present invention decreased by less than 10% after 500 hours. This proves the excellent ability of the "dual interface crosslinking network" to resist long-term chemical-mechanical coupling stress and maintain the integrity of the microstructure, providing a material basis for the ultra-long life operation of VRFB.

[0053] (4) Imparts excellent overall performance to vanadium redox flow batteries: VRFB assembled using the membrane of this invention achieves excellent performance at 150 mA cm⁻¹. -2 At high current densities, it achieves excellent performance with an average coulombic efficiency of ≥99.0% and an average energy efficiency of ≥90.0%. After 3000 charge-discharge cycles, the battery capacity retention rate is as high as 97% or more, and its cycle stability and energy efficiency level far exceed those of batteries using existing commercial or reported separators.

[0054] (5) The preparation process is controllable and has industrialization potential: The preparation method provided by this invention has clear steps and key process parameters (such as solid-liquid ratio, concentration, proportion, heating program, etc.). All raw materials are commercially available. The solution casting method used is mature and reliable, easy to scale up production, and has good prospects for industrial application. Detailed Implementation

[0055] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0056] Example 1

[0057] Preparation of functionalized core-shell hybrid fillers

[0058] (1) Mild etching pretreatment of MXene nanosheets

[0059] Weigh 2.0 g of commercially available Ti3AlC2 MAX phase powder (purity >98%, 200 mesh) and slowly add it to 80 mL of a pre-prepared mixed etchant. The mixed etchant is a mixed aqueous solution of 6 M hydrochloric acid and 1.0 M lithium fluoride (i.e., a solid-liquid ratio of 1 g: 40 mL). Place the mixture in a 40°C water bath and magnetically stir for 24 hours in a fume hood. After the reaction is complete, transfer the reaction solution to a centrifuge tube and repeatedly centrifuge and wash with deionized water (8000 rpm, 10 minutes each time) until the pH of the supernatant is ≥6, yielding a dark green multilayer MXene etching product precipitate.

[0060] The precipitate was redispersed in 200 mL of argon-deoxygenated deionized water and placed in an ice-water bath under continuous argon protection. An ultrasonic cell disruptor was used for intermittent sonication at 100 W (2 seconds on, 1 second off) for a total treatment time of 1.5 hours. Subsequently, the dispersion was centrifuged at 3500 rpm for 1 hour, and the upper layer, a dark green colloidal dispersion exhibiting a pronounced Tyndall effect, was carefully collected. This was the pretreated dispersion of monolayer / few-layer Ti3C2-based MXene nanosheets with surfaces primarily terminated with -O, -OH, and a small amount of -F functional groups, at a concentration of approximately 1.5 mg / mL. X-ray photoelectron spectroscopy (XPS) analysis of the surface revealed that the ratio of the characteristic F 1s peak area to the peak area of ​​the -OH component in the O 1s spectrum was 0.35, satisfying the requirement of -F / -OH < 0.5.

[0061] (2) In-situ growth of gradient bimodal aperture SNW-1 type COF layer

[0062] Measure 100 mL of the pretreated MXene dispersion (containing approximately 150 mg of MXene) into a 250 mL three-necked flask. Add 0.048 g (0.225 mmol) of 1,3,5-tricarboxymethyl phloroglucinol (TFP) and 0.048 g (0.445 mmol) of 1,4-diaminobenzene (DAB) sequentially (TFP to DAB molar ratio 1:1.98). Sonicate for 30 minutes to ensure complete dissolution and dispersion of the monomer. Then add 4.0 mL of glacial acetic acid as a catalyst (approximately 4 vol% of the expected final reaction volume of 100 mL).

[0063] The reaction flask was placed in a temperature-controlled cryogenic bath. First, the reaction was magnetically stirred at 5°C for 4 hours. Then, the temperature was programmed to rise to 70°C at a rate of 0.8°C / min, and the reaction was continued with vigorous stirring at 70°C for 30 hours. After the reaction, the product was washed five times each with N,N-dimethylformamide (DMF) and anhydrous ethanol by centrifugation to completely remove unreacted monomers and catalyst. Finally, the product was dried in a vacuum oven at 60°C for 12 hours to obtain a black MXene / SNW-1 core-shell hybrid material powder, denoted as MC-BP. Characterization by nitrogen adsorption-desorption (BET) testing showed that the material exhibited typical micropore filling characteristics in the relative pressure P / P0 range of 0.1-0.3, with a calculated BET specific surface area of ​​510 m² / g. A significant H4-type hysteresis loop was observed in the P / P0 range of 0.4-0.8, confirming the existence of mesopores in the 2-5 nm range, thus successfully constructing a bimodal pore size distribution.

[0064] (3) Preliminary interfacial modification (silanization) of hybrid fillers

[0065] Weigh 1.0 g of MC-BP core-shell hybrid material powder and disperse it in 150 mL of anhydrous ethanol. Sonicate the mixture for 30 minutes. Add 0.1 mL of γ-aminopropyltriethoxysilane (KH-550, density approximately 0.946 g / mL, mass approximately 0.0946 g, about 9.5% of the filler mass). Refluxing and stirring at 75°C for 6 hours under nitrogen protection. After the reaction, wash three times with anhydrous ethanol by centrifugation and dry under vacuum at 60°C to obtain the hybrid filler with surface-grafted silane coupling agent, denoted as MC-BP-APTES.

[0066] Example 2

[0067] Preparation of a high ion-selective perfluorosulfonic acid ion exchange membrane (filler content 2 wt%)

[0068] Weigh 10.0 g of N,N-dimethylformamide (DMF) solution (containing 0.50 g of PFSA resin dry weight) containing 5 wt% perfluorosulfonic acid resin (purchased from Alibaba Global Direct Procurement Platform, model 1000KE, equivalent weight EW=1000). Add 0.010 g of MC-BP-APTES filler prepared in Example 1 (accounting for 2% of the dry weight of PFSA resin in the target dry film, i.e., the target mass fraction of filler is approximately 1.96%). Then add 0.002 g of polyethylene glycol diglycidyl ether (PEGDE, Mn=500) as a flexible organic crosslinking agent (its mass is approximately 21% of the amount of silane coupling agent KH-550 added). The mixture is first ultrasonically treated at 300 W for 1 hour, and then continuously stirred at 500 rpm for 24 hours on a planetary mixer to obtain a uniform and stable casting solution. The total solid mass of the casting solution (0.50 + 0.010 + 0.002 = 0.512 g) accounts for approximately 5.1% of the total mass of the casting solution (approximately 10.012 g).

[0069] The casting solution was poured onto a flat, clean glass plate, and an automatic film scraper was used to control the wet film thickness to 200 μm. The glass plate was then transferred to a forced-air drying oven, and the following gradient temperature drying and curing procedure was followed: First stage: 50℃, 4 hours, to evaporate most of the solvent; Second stage: 120℃, 8 hours, this stage is the main in-situ crosslinking reaction period, during which the amino groups of the silane coupling agent react with the epoxy groups of PEGDE, and PEGDE combines with the PFSA matrix through hydrogen bonding and other interactions to form a double crosslinking network; Third stage: 150℃, 1 hour, used to eliminate internal stress, further promote crosslinking, and improve the thermal stability of the film. After the procedure, the film was allowed to cool naturally to room temperature, and then carefully peeled off the glass plate to obtain a transparent, flexible composite film with a thickness of approximately 50 μm, denoted as PFSA / MC-BP-2%-Dual.

[0070] Example 3

[0071] Preparation of ion exchange membranes with different filler contents

[0072] Following the exact same process as in Example 2, only the amount of MC-BP-APTES filler added was changed, and composite films with filler accounting for 1% and 3% of the dry weight of PFSA resin were prepared, respectively, denoted as PFSA / MC-BP-1%-Dual and PFSA / MC-BP-3%-Dual.

[0073] Comparative examples (to verify the inventiveness and synergistic effect of key features of the present invention)

[0074] Comparative Example 1 (CP1): Preparation and Properties of High-Fluorine (F)MXene Etched by Conventional HF Etching

[0075] (1) Preparation of MXene nanosheets with high fluorine surface

[0076] Take 2.0 g of Ti3AlC2 MAX phase powder and slowly add it to 40 mL of 40 wt% hydrofluoric acid aqueous solution. Stir continuously at 35℃ for 24 hours. After the reaction is completed, wash repeatedly with deionized water by centrifugation (8000 rpm, 10 minutes / time) until the pH of the supernatant rises to 6.

[0077] The resulting multilayer precipitate was dispersed in 200 mL of deionized water and ultrasonically exfoliated at 150 W for 1.5 hours under argon protection. Subsequently, it was centrifuged at 3500 rpm for 1 hour, and the upper colloidal dispersion was collected, which is the MXene nanosheet dispersion etched by conventional HF etching, denoted as HF-MXene. X-ray photoelectron spectroscopy analysis of HF-MXene confirmed that its surface -F / -OH molar ratio was 2.8:1.

[0078] (2) Preparation of core-shell hybrid fillers and composite membranes

[0079] All subsequent steps, including the in-situ growth of SNW-1 type COF, modification with silane coupling agent, and co-casting with perfluorosulfonic acid resin, strictly followed the process and parameters of Examples 1 and 2 of this invention. The final composite membrane was denoted as PFSA / HF-MXene-COF-2.

[0080] Comparative Example 2 (CP2): Composite membrane with a single microporous COF shell

[0081] In step (2) of Example 1, the gradient heating step was omitted, and the mixture was directly reacted at a constant temperature of 70°C for 34 hours, with all other conditions remaining unchanged. This method yielded an MXene / COF hybrid material with only a microporous structure (denoted as MC-MP). Subsequent steps were the same as in Example 2, preparing a composite membrane containing 2 wt% filler, denoted as PFSA / MC-MP-2%-Dual.

[0082] Comparative Example 3 (CP3): Single-interface film without flexible crosslinking agent

[0083] In the preparation of the casting solution in Example 2, no polyethylene glycol diglycidyl ether (PEGDE) flexible crosslinking agent was added; only filler treated with a silane coupling agent was used. All other steps were identical, and the resulting membrane was designated PFSA / MC-BP-2%-Single.

[0084] Comparative Example 4 (CP4): Physically blended membrane

[0085] In step (3) of Example 1, no silane coupling agent treatment was performed. The MC-BP core-shell hybrid material powder was directly and physically mixed with the PFSA solution without adding any crosslinking agent. A composite membrane containing 2 wt% filler was prepared, denoted as PFSA / MC-BP-2%-Blend.

[0086] Comparative Example 5 (CP5): Commercial Nafion 212 membrane

[0087] As a performance benchmark.

[0088] Performance Testing and Results Analysis

[0089] 1. Physicochemical and electrochemical performance testing

[0090] All membrane samples were pretreated in 1.0 M H₂SO₄ solution at 80°C for 1 hour before testing to ensure complete conversion to H₂SO₄. + Type. Proton conductivity was determined by electrochemical impedance spectroscopy (EIS) at 25°C and 100% relative humidity. VO 2+ Permeability was determined using the diffusion cell method. The diffusion cell contained 1.5 M VOSO4 in 3.0 M H2SO4 and 1.5 M MgSO4 in 3.0 M MH2SO4 solutions on either side. The concentration of vanadium ions in the receiving cell was monitored periodically using a UV-Vis spectrophotometer. The test results are shown in Tables 1 and 2.

[0091] Table 1 Comparison of basic physicochemical and electrochemical properties of various ion exchange membranes

[0092]

[0093] Table 2 Comparison of ion selectivity of various ion exchange membranes

[0094]

[0095] Results analysis: The ion selectivity coefficient of the membrane (PFSA / MC-BP-2%-Dual) of this invention is 97.4 × 10⁻⁶. 5 The S·min / cm³ ratio reaches that of commercially available Nafion 212 membranes (60.0×10⁻⁶). 5 This is 16.2 times that of the previous model (S·min / cm³). This is due to the synergistic effect of the "rich-OH MXene core", "bimodal porous COF shell" and "double cross-linking interface". The comparative examples CP1-CP4 (performance ratios of 1.4 to 5.0) successively verified the necessity of each technical feature.

[0096] Each comparative example, by successively omitting or altering key technical features of the present invention, forms a clear performance gradient (1.4 times to 5.0 times), which in turn proves the necessity and synergy of each feature:

[0097] CP4 (physical blend, 1.4x): Performance close to the baseline, proving that without interface treatment, the filler is incompatible with the matrix and may even introduce defects.

[0098] CP1 (high F / OH ratio MXene core, 3.4 times): The CP1 membrane has an excessively high F / OH ratio on the MXene core surface, which leads to impeded proton conduction at the interface and easy formation of leakage channels. Its performance is significantly lower than that of this invention. This directly proves that the "-F / -OH molar ratio less than 0.5:1" on the MXene core surface is a necessary condition for constructing an efficient proton transport interface and achieving high ion selectivity.

[0099] CP2 (single micropore COF, 4.0 times): The low proton conductivity indicates that the mesopores in the bimodal pore structure are crucial for maintaining high-speed proton conduction.

[0100] CP3 (without flexible crosslinking, 5.0 times): Its performance is significantly inferior to that of the present invention (16.2 times), confirming that the dual crosslinking network has an irreplaceable role in strengthening the interface and blocking insulators.

[0101] This analysis shows that the effect of any single improvement is limited, and the present invention achieves a leap in performance through the synergy of the three.

[0102] 2. Accelerated testing of long-term chemical stability

[0103] Each membrane sample was immersed in a 3.0 M H2SO4 solution at 90℃, periodically removed, washed with deionized water, and reequilibrated under standard conditions (25℃, 100% relative humidity). Its ion selectivity coefficient was then tested for 500 hours. By comparing the initial and 500-hour ion selectivity coefficients, the performance retention rate of each sample under extreme chemical conditions was calculated, and the results are shown in Table 3.

[0104] Table 3. Results of accelerated stability experiments for different groups

[0105]

[0106] Results Analysis: As shown in Table 3, the PFSA / MC-BP-2%-Dual membrane prepared in this invention maintained a performance retention rate of 93.5% and a degradation rate of only 6.5% after 500 hours of accelerated aging in strong acid, demonstrating significantly better stability than all comparative examples. In particular, compared to the CP3 membrane (41.8% degradation rate) lacking a flexible crosslinking network and the CP4 membrane (54.9% degradation rate) of simple physical blending, the stability advantage of the membrane in this invention is extremely significant. This strongly demonstrates that the "dual-interface crosslinking network" can endow the filler-matrix interface with exceptional chemical durability and mechanical toughness, which is the fundamental reason for ensuring the integrity of the composite membrane's microstructure under long-term harsh operating conditions, thus achieving ultra-long-life operation. While the commercial Nafion 212 membrane (CP5) used as a benchmark has acceptable chemical stability (13.0% degradation rate), its initial ion selectivity coefficient is extremely low (see Table 1), therefore its absolute performance is still far inferior to that of the membrane in this invention. Meanwhile, the performance degradation rate (18.5%) of the comparative CP1 (high F / OH ratio MXene core) was also significantly higher than that of the film of this invention. This indicates that the MXene core that failed to meet the requirement of '-F / -OH molar ratio less than 0.5:1' is more fragile at the interface with the substrate and COF shell under long-term strong acid conditions, further confirming the key role of this surface chemical characteristic in maintaining the long-term stability of the interface.

[0107] 3. Performance Testing of Vanadium Redox Flow Batteries

[0108] A single-cell battery with an effective area of ​​25 cm² was assembled using the above-mentioned membrane, with 30 mL of 1.6 MV electrolyte for both positive and negative electrodes. 3+ / V 4+ In 3.0 M H₂SO₄ solution. At 150 mA cm⁻¹ -2 Charge-discharge cycle tests were conducted at a constant current density, with a charging cutoff voltage of 1.65 V and a discharging cutoff voltage of 1.0 V.

[0109] The test results (average values ​​for laps 100-200 and data after 3000 laps) are shown in Table 4.

[0110] Table 4. Performance comparison of VRFB single cells using different ion exchange membranes

[0111]

[0112] Results Analysis: The battery using the membrane of this invention achieved a coulombic efficiency (99.3%) close to the theoretical limit and an energy efficiency exceeding 90%. More importantly, after 3000 long cycles, its capacity retention rate reached 97.5%, demonstrating excellent cycle stability. In contrast, the capacity decay of the comparative batteries (especially CP3 and CP4) was significantly faster, directly confirming the decisive influence of interface engineering on the actual long-life operation of the battery.

[0113] This invention creatively integrates three key technical features: "mild etching of a -OH MXene-rich core," "gradient growth of a bimodal porous COF shell," and "silane-flexible molecular dual crosslinking interface." Through ingenious multi-level structural design, it generates a super synergistic effect of "1+1+1 >> 3." The prepared perfluorosulfonic acid ion-exchange membrane not only achieves an order-of-magnitude improvement in ion selectivity but also simultaneously solves the challenge of balancing high proton conduction with long-term stable operation. When applied to a vanadium redox flow battery, it achieves excellent comprehensive performance, approaching the theoretical limit in coulombic efficiency, exceeding 90% in energy efficiency, and retaining 97.5% of capacity after 3000 cycles. The technical solution and effects of this invention far surpass existing technologies, possessing outstanding substantive features and significant progress, and have broad prospects for industrial application.

[0114] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0115] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high-ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries, characterized in that, The ion-exchange membrane comprises: Perfluorosulfonic acid polymer matrix; A functionalized core-shell hybrid filler uniformly dispersed in the perfluorosulfonic acid polymer matrix, wherein the functionalized core-shell hybrid filler comprises: a) Core layer: The core layer is an MXene nanosheet that has undergone etching pretreatment, and the molar ratio of -F functional groups to -OH functional groups in the pretreated MXene nanosheet is less than 0.5:1; b) Shell: The shell is an SNW-1 type covalent organic framework layer grown in situ on the surface of pretreated MXene nanosheets. The SNW-1 type covalent organic framework layer has a bimodal pore size distribution, including inherent micropores of 0.5-0.8 nm and mesopores of 2-5 nm generated in situ within the SNW-1 type covalent organic framework layer. A dual-interface cross-linked network, which is composed of the following substances: i. A silane coupling agent, wherein one end of the silane coupling agent can form a Si-O-Ti covalent bond with the -OH group on the surface of MXene, and the other end contains an amino or epoxy group that can interact with the perfluorosulfonic acid polymer matrix; ii. Flexible organic crosslinking agents; The functionalized core-shell hybrid filler has a mass fraction of 0.5-5 wt% in the ion exchange membrane. The total mass fraction of the silane coupling agent and the flexible organic crosslinking agent is 0.1-1.5 wt%, and the mass ratio of the two is 1:0.2-1:

1.

2. The ion exchange membrane according to claim 1, characterized in that, The silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane; The flexible organic crosslinking agent is polyethylene glycol diglycidyl ether.

3. The method for preparing the high ion-selectivity perfluorosulfonic acid ion-exchange membrane for vanadium batteries according to any one of claims 1 or 2, characterized in that, Includes the following steps: (1) Mild etching pretreatment of MXene nanosheets: Ti3AlC2 MAX phase powder was dispersed in a mixed etchant and stirred at 30-50℃ for 12-36 h. After the reaction was completed, the product was centrifuged and washed until neutral to obtain a multilayer MXene etched product in which interlayer Al was selectively etched. The multilayer MXene etching product was subjected to low-power ultrasonic exfoliation under a protective atmosphere to dissociate the interlayers and obtain a dispersion of pretreated MXene nanosheets with one or fewer layers. (2) In-situ growth of gradient bimodal aperture SNW-1 type covalent organic framework layer: The dispersion of the pretreated MXene nanosheets obtained in step (1) was mixed with 1,3,5-tricarboxymethyl phloroglucinol, 1,4-diaminobenzene and glacial acetic acid, and the reaction was carried out by gradient heating method to obtain an SNW-1 type covalent organic framework layer with bimodal pore size distribution grown in situ on the surface of the pretreated MXene nanosheets, that is, a core-shell hybrid filler of MXene and SNW-1 type covalent organic framework. The gradient heating method includes: first reacting at 0-10℃ for 2-6 hours, then increasing the temperature to 60-80℃ at a rate of 0.5-1℃ / min, and continuing the reaction at this temperature for 20-40 hours; (3) Preliminary interface modification of hybrid fillers: The core-shell hybrid filler obtained in step (2) is dispersed in anhydrous ethanol, a silane coupling agent is added, and the mixture is refluxed at 60-80℃ for 4-8 hours to obtain a hybrid filler with a surface grafted silane coupling agent. (4) Preparation of casting solution and secondary cross-linking of interface: The hybrid filler with surface-grafted silane coupling agent obtained in step (3), perfluorosulfonic acid resin solution and flexible organic crosslinking agent are dissolved in organic solvent and a uniformly dispersed casting solution is formed under ultrasonication and stirring. (5) Solution casting and in-situ curing: The casting solution obtained in step (4) is cast onto a flat substrate and subjected to gradient temperature drying: first, it is dried at 40-60℃ for 2-4 hours, then treated at 100-130℃ for 4-10 hours, and finally heat-treated at 140-160℃ for 0.5-2 hours to obtain the high ion selectivity perfluorosulfonic acid ion membrane.

4. The preparation method according to claim 3, characterized in that, In step (1), the mass-to-volume ratio of the Ti3AlC2 MAX phase powder to the mixed etchant is 1 g : 30-60 mL; The mixed etchant is a solution of concentrated hydrochloric acid and lithium fluoride, wherein the final concentration of concentrated hydrochloric acid in the mixed etchant is 6-9 M and the final concentration of lithium fluoride is 0.5-2.0 M. The low-power ultrasonic ablation process is as follows: ultrasonic ablation is performed for 0.5-2 hours under argon or nitrogen protection with a power of 50-150 W.

5. The preparation method according to claim 3, characterized in that, The gradient heating procedure in step (2) is as follows: first react at 5℃ for 4 hours, then heat to 70℃ at 0.8℃ / min, and maintain at 70℃ for 30 hours.

6. The preparation method according to claim 3, characterized in that, In step (2), based on the mass of MXene nanosheets contained in the pretreated MXene nanosheet dispersion, the amount of 1,3,5-tricarboxymethyl phloroglucinol added is 10-40 mmol / g; the molar ratio of 1,4-diaminobenzene to 1,3,5-tricarboxymethyl phloroglucinol is 1.5-2.0:1; and the amount of glacial acetic acid added accounts for 3-8 vol of the total volume of the reaction system.

7. The preparation method according to claim 3, characterized in that, In step (3), the dispersion concentration of the core-shell hybrid filler in anhydrous ethanol is 2-10 mg / mL; the amount of silane coupling agent added is 5-20% of the mass of the core-shell hybrid filler.

8. The preparation method according to claim 3, characterized in that, The organic solvent in step (4) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; In step (4), the mass ratio of the hybrid filler of the surface-grafted silane coupling agent to the dry weight of the perfluorosulfonic acid resin is 0.5-5:100; the total solid content of the casting solution is 5-15 wt%.

9. A vanadium redox flow battery, characterized in that, The high ion-selectivity perfluorosulfonic acid ion membrane prepared by the method described in any one of claims 1 or 2 or any one of claims 3-8 is used as the battery separator.

10. The all-vanadium redox flow battery according to claim 9, characterized in that, At a current density of 150 mA cm⁻¹ -2 Under the conditions of charge and discharge testing, the average coulombic efficiency is not less than 99.0%, the average energy efficiency is not less than 90.0%, and after 3000 charge and discharge cycles, the battery capacity retention rate is not less than 97%.

Citation Information

Patent Citations

  • Porous crystalline core-shell hybrid material based on UiO-66@SNW-1 as well as preparation method and application of porous crystalline core-shell hybrid material

    CN108273555A

  • Zwitterion conductive membrane for flow battery, and preparation method therefor

    WO2023272821A1